Risk factors for suicide in prisons: a systematic review and meta-analysis - Zhong, S; Senior, M; Yu, R; Perry, A; Hawton, K; Shaw, J; Fazel, S (Elsevier, 2021)
Background Rates of suicide among people in prison are elevated compared with people of similar age and sex who are living in the community. Improving assessments and interventions to reduce suicide risk requires updated evidence on risk factors. We aimed to examine risk factors associated with suicide in prisoners. Methods We did an updated systematic review and meta-analysis of risk factors for suicide among people in prison. We searched five biblographic databases for articles published between Jan 1, 2006, and Aug 13, 2020, and one database for articles published between Jan 1, 1973, and Aug 13, 2020. Eligible studies reported risk factors in individuals who died by suicide while in prison and in controls from the general prison population. Two reviewers independently extracted data for each study using a standardised form. We calculated random-effects pooled odds ratios (ORs) for the association of suicide with demographical, clinical, criminological, and institutional risk factors, and investigated heterogeneity using subgroup and meta-regression analyses. This systematic review is registered with PROSPERO, CRD42020137979. Findings We identified 8041 records through our searches, and used 77 eligible studies from 27 countries, including 35 351 suicides, in the main analysis. The strongest clinical factors associated with suicide were suicidal ideation during the current period in prison (OR 15·2, 95% CI 8·5–27·0), a history of attempted suicide (OR 8·2, 4·4–15·3), and current psychiatric diagnosis (OR 6·4, 3·6–11·1). Institutional factors associated with suicide included occupation of a single cell (OR 6·8, 2·3–19·8) and having no social visits (OR 1·9, 1·5–2·4). Criminological factors included remand status (OR 3·6, 3·1–4·1), serving a life sentence (OR 2·4, 1·3–4·6), and being convicted of a violent offence, in particular homicide (OR 3·1, 2·2–4·2). Interpretation Several modifiable risk factors, such as psychiatric diagnosis, suicidal ideation during the current period in prison, and single-cell occupancy, are associated with suicide among people in prison. Preventive interventions should target these risk factors and include improved access to evidence-based mental health care. Understanding other factors associated with suicide might improve risk stratification and resource allocation in prison services. Funding Wellcome Trust, National Institute for Health Research Applied Research Collaboration Oxford and Thames Valley.